PENGARUH MOTIF PENGGUNAAN MEDIA SOSIAL INSTAGRAM DAN KUALITAS INFORMASI PADA AKUN @TABU.ID TERHADAP KEPUASAN FOLLOWERS TERKAIT SEX EDUCATION - Farrah Devanti Tri Putri; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Currently, social media users have experienced rapid development throughout the world, including in Indonesia. One of the most widely used social media in conveying various information is Instagram. Through social media, the @tabu.id account delivers information about education and health which is still taboo by most people. This research was conducted to determine how much influence the motive for using social media Instagram and the quality of information on the @tabu.id account on followers satisfaction related to sex education partially and simultaneously. The theory used in this research is use and gratification.The method used in this study is a quantitative explanation method with sampling techniques in the form of non probability sampling and purposive sampling approach techniques. The population in this study was 70,000 followers with a sample size of 398 respondents. Collecting data in this research is by using a questionnaire.Based on multiple linear regression analysis, the research regression equation is obtained, namely Y = 0.550 + 0.573 X1 + 0.358 X2. Through the t test and F test, the significance value of each test is 0.000 <0.05. This means that all alternative hypotheses (Ha) are accepted and the null hypothesis (H0) is rejected either partially or simultaneously. The Pearson product moment correlation coefficient test shows that the level of influence between the motives for using social media Instagram X1 on the satisfaction of followers Y is 0.725 with a strong category. Then the level of influence between the qualities of information X2 on the satisfaction of followers Y is 0.591 in the medium category. The multiple correlation coefficient test shows that the level of influence between the motive for using social media Instagram X1 and the quality of information X2 on the satisfaction of followers Y is 0.765 with the strong category. The coefficient of determination test shows the contribution of the influence of the motive for using Instagram social media and the quality of information on follower’s satisfaction is 58.5%. While the remaining 41.5% influenced by other factors outside of this study. Keywords: motive, quality of information, satisfaction, Instagram, @tabu.id, sex education